A Review of Common Problems in Design and Installation of Water Spray Cooling and Low Expansion Foam System to Protect Storage Tanks Containing Hydrocarbons Against Fires - I. Alimohammadi; Farshad Nouraei; Mohammad Javad Daryalaal; Masoud Ghasemi (Iranian Journal of Health, Safety and Environment, 2015)
Tank fires are rare but carry significant potential risk to life and property. For this reason fire protection of tanks is critical. Fixed Low expansion foam and water spray cooling systems are one of the most effective and economical ways to reduce damages to a tank from fire. Such systems are currently installed in many companies but are not effective enough and require involvement of firefighters which in turn threaten their lives. This paper studies in a systematic way the problems of foam and cooling systems currently installed in a few domestic companies which operate storage tanks with focus on floating and fixed roof atmospheric tanks containing hydrocarbons and offers possible solutions for more efficient installation, design and operation of such systems.